A3.16 Serum S100A4 correlates with skin fibrosis, lung involvement and disease activity in systemic sclerosis. (31st January 2014) - Tomcik, Michal; Andres Cerezo, Lucie; Skacelova, Simona; Komarc, Martin; Becvar, Radim; Grigorian, Mariam; Distler, Joerg H W; Senolt, Ladislav
Abstract : Background: In our previous study we demonstrated that S100A4 is overexpressed in scleroderma (SSc) skin, fibroblasts and preclinical models of SSc in a TGF-β dependent manner. We showed that S100A4 is a new regulator of TGF-β signalling and its inhibition prevents the stimulatory effects of TGF-β. Inactivation of S100A4 prevented dermal fibrosis induced by bleomycin and in Tsk-1 mice. Objectives: To evaluate S100A4 in sera of SSc patients and characterise its potential association with SSc-related features. Materials and Methods: A total of 33 patients (29 females; mean age 52.8; disease duration 4.2 years; dcSSc/lcSSc = 8/25) who met the ACR classification criteria for SSc and 20 healthy individuals matched by age and sex were included in this study. Serum S100A4 levels were measured using ELISA (CycLex Co., Ltd., Nagano, Japan). CRP, ANA and ENA complex were evaluated. SSc-related manifestations were obtained from the Czech Registry Database of SSc patients. Skin changes were assessed using the modified Rodnan skin score (mRSS) and EUSTAR SSc activity score was determined. Data are presented as mean ± SEM. Results: S100A4 serum levels were significantly increased in SSc patients compared with healthy controls (119.2 ± 23.4 vs. 43.9 ± 3.3ng/ml, p = 0.011). Patients with diffuse cutaneous SSc had significantly higher levels of serum S100A4 compared with patients with limited cutaneous SSc or healthy controls (201.8 ± 53.1 vs. 92.7 ± 24.0ng/ml, p = 0.017 and 201.8 ± 53.1 vs. 43.9 ± 3.3ng/ml, p = 0.001, respectively). Levels of S100A4 positively correlated with mRSS (r = 0.556, p = 0.001). Furthermore, S100A4 levels negatively correlated with forced vital capacity (FVC) and saturation of peripheral oxygen (SPO2) (r = - 0.362, p = 0.038 and r = -0.414, p = 0.029, respectively). Of particular interest, S100A4 levels positively correlated with EUSTAR SSc activity score (r = 0.750, p = 0.0001). However, only correlations between S100A4 and mRSS, and S100A4 and EUSTAR SSc activity score were approved at corrected level of statistical significance after Bonferroni's correction (p<0.01). The presence of autoantibodies (ANA, anti-centromere, anti-Scl70), pathological capillaroscopic pattern (early, active or late), and presence of the main individual clinical symptoms of SSc did not significantly affect levels of serum S100A4. Conclusions: We demonstrate that S100A4 serum levels are significantly increased in SSc patients compared with healthy controls. Higher levels of S100A4 are associated with dcSSc subset, skin involvement, deteriorated parameters of lung involvement and higher disease activity. These data support our previous findings on the role of S100A4 as a regulator of TGF-β induced fibroblast activation and dermal fibrosis in SSc. Acknowledgements: This study was supported by IGA NT 13698-4.